A Wireless Powering and Communication System for Implantable Devices Based on a Royer Oscillator with Radio and Near-field Communication Links. (2015) - Bakula, Marko; Pelgrims, Patrick; Puers, Robert
Abstract: A compact wireless power and communication development system for implantable devices was designed and tested with two receiver circuits based on a 433 MHz separate RF link and near-field communication link using the power transfer field. Operating ranges were 9 and 6 cm respectively. The power transmitter was designed around a Royer oscillator with the possibility of power control and frequency control using a unique Schottky varactor method allowing 560 kHz frequency shift.